Penerapan Pendekatan Humanistik Dalam Pengembangan Kurikulum Merdeka Di Sekolah Menengah Atas - Arnol Arnol; Rusmita Rusmita; Fadriati Fadriati (Departement of Mathematics Education, 2024)
The aim of this research is to describe the application of the humanistic approach to independent curriculum development:. In this article, the research method analysis adopts a combined method between Literature Review and qualitative methods from various available sources. This type of method will combine two methods of data collection, namely apart from collecting data from various previous studies, it will also collect data involving collecting primary data through observation and interviews with the principal and curriculum development team at SMAN 1 Sawahlunto. Based on the results of research carried out, the application of a humanistic approach to independent curriculum development at SMAN 1 Sawahlunto is guided by the characteristics of a humanistic approach to curriculum development, namely 1) objectives and functions. where the curriculum developed has the aim and function of being a guide for organizing subject matter, determining the direction and progress of education by considering the individual, social and economic aspects of school curriculum users. 2) The curriculum development method emphasizes the importance of good emotional relationships between educators and students as the main foundation in the learning process. 3) In developing the curriculum organization at SMAN 1 Sawahlunto, it emphasizes the integrity of students, creating a comprehensive learning experience design, namely by designing learning activities that cover the intellectual, emotional and action aspects of students as well as designing a relevant experience-based curriculum that is linked to the concept of life. daily.